Analisis Kebutuhan Pengembangan Lembar Kerja Peserta Didik berbasis High OrderThinking Skills Kelas X SMA - B, Nurhayati; M, Nuramina; Arsal, Andi Faridah (Biosel Biology Science and Education, 2023)
Student Worksheet (LKPD) Based on High order thinking skills (HOTS) with the aim of producing LKPD that is valid, practical and effective. This type of research is Research and development (R&D) with the ADDIE development model which has five stages, namely analysis, design, development, implementation and evaluation. This student worksheet based on high-level thinking skills aims to foster the creative spirit of students and improve higher-order thinking skills in accordance with the competence of applying HOTS in learning activities. This study aims to determine the level of validity, practicality, and effectiveness of the developed worksheets. The population of this study amounted to 22 students and 2 biology teachers as respondents. Data on validity and practicality were obtained using the questionnaire response method. The research data were analyzed using an assessment rubric. The results of the analysis of the validity and practicality of LKPD with a total average of 80% for the teacher's response is 92% and for the student response is 85.76%. Based on these data, it can be concluded that the development of LKPD is in the very practical category.